APPLICATION OF THE SYSTEM DEVELOPMENT LIFE CYCLE (SDLC) METHOD FOR MOBILE BASED ACADEMIC INFORMATION SYSTEM DESIGN - Handoko Pangestu Girsang; Rima Tamara Aldisa (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This research aims to investigate the application of the SDLC (System Development Life Cycle) Method in designing and building a mobile-based Academic Information System. This is a crucial component in data management and administration in today's educational institutions. With advances in mobile technology, platform integration becomes important to increase the responsiveness of Academic Information Systems. Through the SDLC method, this research will identify systematic steps in mobile-based development, starting from analyzing user needs to implementation and evaluation. Requirements analysis will focus on a deep understanding of user needs and the expected functionality of the System. Initial prototype development will be carried out iteratively to ensure system responsiveness across various mobile platforms. Implementation of the system will involve careful end-user testing to ensure acceptance and effective use. It is hoped that the results of this research will provide guidance for educational institutions that wish to use mobile-based academic systems to increase administrative efficiency and improve the quality of academic services for staff and students.